Elemen Financial Ratios Atas Net Earnings Per Share PT Bank Syariah Indonesia Tbk - Mubarok, Husni; Fuadatis Sholikha, Akhris; Lesmana, Hendra; Suryanti, Ery; Cahya Putri Utami, Bernadette; Muarrifah, Safrina; Tanwirotul Fadlilah, Lilik (Jurnal Sistem Informasi Akuntansi (JASIKA), 2024)
The main purpose of writing is to collect problem formulas from statistical products. Financial Element Factor Analysis Ratios of Net Earnings Per Share of PT Bank Syariah Indonesia Tbk 2000-2022. The research method exploits quantity case studies with descriptive creations, purposive sampling exploits secondary information on financial reports for 23 years listed on the IDX and exploits IBM SPSS with Analyze Compare Means One Sample T Test and Linear Regression. Scientific findings, especially from testing segmental assumptions that have been carried out by the beta ROE indicator, amplifying coefficients, show that the most impact is 1.180 with a positive value relevant to the level of Strongest correlation. This summary proves that together the entity independent factor of 0.793 has a relevant positive value.